2014
DOI: 10.1152/ajprenal.00218.2014
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 promotes proliferation of collecting duct kidney epithelial cells through ERK activation and increased glycolysis in polycystic kidney disease

Abstract: Polycystic kidney disease (PKD) is a common genetic disorder leading to cyst formation in the kidneys and other organs that ultimately results in kidney failure and death. Currently, there is no therapy for slowing down or stopping the progression of PKD. In this study, we identified the disintegrin metalloenzyme 17 (ADAM17) as a key regulator of cell proliferation in kidney tissues of conditional knockout Ift88 −/− mice and collecting duct epithelial cells from Ift88° rpk mice, animal models of autosomal rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
21
0
3
Order By: Relevance
“…Numerous studies have shown that the activation of the ERK1/2 signaling pathway is involved in regulating the proliferation of various cells, including kidney epithelial cells [ 18 ], smooth muscle cell [ 19 ], melanoma cell [ 20 ], and preadipocytes [ 11 ]. Accordingly, in the present study, the ERK1/2 signaling pathway was activated by [Ca 2+ ] o and the activation of ERK1/2 was abolished by NPS2143.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the activation of the ERK1/2 signaling pathway is involved in regulating the proliferation of various cells, including kidney epithelial cells [ 18 ], smooth muscle cell [ 19 ], melanoma cell [ 20 ], and preadipocytes [ 11 ]. Accordingly, in the present study, the ERK1/2 signaling pathway was activated by [Ca 2+ ] o and the activation of ERK1/2 was abolished by NPS2143.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway, which consists of extracellular signal-regulated kinase 1/2 (ERK1/2), Jun kinase (JNK), and p38 MAPK, plays an important role in controlling cell proliferation in mammalian cells [ 17 ]. In particular, ERK1/2 is involved in the proliferation of various cells, such as kidney epithelial cells [ 18 ], smooth muscle cell [ 19 ], melanoma cell [ 20 ], and preadipocytes [ 11 ]. ERK elicits its role in cell proliferation possibly through its effect on the cell cycle transition from the G0/G1 phase to the S phase [ 21 ] and/or on the expression of cyclin D [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified 2 sheddases of LRP-1 in chondrocytes, ADAM-17 and MMP-14 (12). Kidney epithelial cells with the identical IFT88 ORPK mutation have previously been described to have elevated ADAM-17 (45), but, in contrast, we found that IFT88 ORPK chondrocytes expressed similar or lower levels of ADAM-17 than wild-type chondrocytes (Fig. 3B); however, we found increased cellular expression of MMP-14 in IFT88 ORPK chondrocytes compared with wild-type cells (Fig.…”
Section: Disruption Of Ift88 Stimulates Lrp-1 Sheddingmentioning
confidence: 99%
“…Besides, Warburg effect accelerates the process of PKD by activating the disintegrin metalloenzyme 17 (ADAM17) (Beck Gooz et al, ). Moreover, ADAM17 can promote proliferation of collecting duct kidney epithelial cells by increasing glycolytic shift via EGFR/MAPK/ERK pathway in PKD cells.…”
Section: Warburg Effect Accelerates Cyst Expansion In Pkdmentioning
confidence: 99%